Solution‐Processed Chalcopyrite Solar Cells: the Grain Growth Mechanism and the Effects of Cu/In Mole Ratio. Issue 6 (26th December 2021) - Yu, Shaotang; Li, Bingyan; Jiang, Jingjing; Liu, Xinge; Hao, Shasha; Han, Shuaiqi; Yan, Weibo; Xin, Hao
Abstract: Solution‐processed Cu(In, Ga)(S, Se)2 solar cells have reached 18% efficiency but still remain much lower compared to state‐of‐the‐art vacuum based solar cells. In comparison to vacuum deposited precursor films, which mostly consist of stacked metal and/or metal chalcogenide layers and takes a liquid Cu2− x Se assisted grain growth mechanism, solution‐processed precursor films normally have a chalcopyrite structure that is already developed. Understanding the grain growth mechanism of solution‐processed absorbers is crucial to control the electronic properties and further improve the device photovoltaic performance. Here, the grain growth mechanism of a N ‐methyl‐pyrrolidone solution processed precursor film with composition from Cu‐poor to Cu‐rich is systematically investigated. Characterizations show that the chalcopyrite structured CuInS2 precursor film takes a direct phase transformation grain growth mechanism and forms the CuIn(S, Se)2 (CISSe) absorber without the presence of a detrimental Cu2− x Se phase with Cu/In ratio up to unit. Beyond the stoichiometric composition, the coexistence of Cu2− x Se facilitates grain growth but deteriorates device performance. The direct phase transformation mechanism not only avoids detrimental Cu2− x Se but also enables fabrication of a highly efficient CISSe device near stoichiometric composition with high tolerance to the Cu/In ratio (from 0.90 to 1.05). By preliminary optimization, a CISSe solar cell with an efficiency of 13.6% is achieved in ambient air with a Cu/In ratio of 0.93. Abstract : Direct phase transformation grain growth mechanism is demonstrated from a solution‐processed chalcopyrite structured precursor film, which enables fabrication of a highly efficient CuIn(S, Se)2 (CISSe) solar cell near stoichiometric composition without the detrimental Cu2− x Se due to its high tolerance to the Cu/In ratio (from 0.90 to 1.05). By preliminary optimization, a 13.6% efficient CISSe device is fabricated from an N ‐methyl‐pyrrolidone solution processed in ambient air.